Improving Student’s Critical Thinking Ability Through Guided Discovery Learning Methods Assisted by Geogebra - Batubara, Ismail Hanif (International Journal for Educational and Vocational Studies, 2019)
This research is aimed to know: (1) Whether the increasing student’s critical thinking ability through guided discovery learning methods assisted by geogebra higher than the students who were given guided discovery methods without geogebra, (2) How the interaction between learning and early math  ability of student mathematical learning result. This study was a quasi-experimental study. The population of this study was the entire class of six semester mathematics education which approximately 184 people. Randomly, two classes were selected from six classes.  The first experimental class was given a geogebra assisted discovery method and the second experimental class was given a guided discovery method without  geogebra . The instrument used was a description test. The data analysis has been done by analysis of two-way variance (ANOVA). The results showed (1) the increasing student’s critical thinking ability through guided discovery learning methods assisted by geogebra were better than the students who were given guided discovery learning methods without geogebra. (2) There was no Interaction between learning and early math ability of student mathematical learning results.